Delimitations of Latin American Philosophy : Beyond Redemption - Rivera, Omar (Book collections on Project MUSE., 2019)
"A distinctive focus of 19th- and 20th-century Latin American philosophy is the convergence of identity formation and political liberation in ethnically and racially diverse postcolonial contexts. From this perspective, Omar Rivera interprets how a "we" is articulated and deployed in central political texts of this robust philosophical tradition. In particular, by turning to the work of Peruvian political theorist Jose Carlos Mariátegui among others, Rivera critiques philosophies of liberation that are invested in the redemption of oppressed identities as conditions for bringing about radical social and political change, foregrounding Latin America's complex histories and socialities to illustrate the power and shortcomings of these projects. Building on this critical approach, Rivera studies interrelated epistemological, transcultural, and aesthetic delimitations of Latin American philosophy in order to explore the possibility of social and political liberation "beyond redemption.""--